Accidents in the evolution of the burned - Hazán, Enrique; Grolero de Cat, María Luisa; Castro, Omar; Delfino, Heriberto (Cirugía del Uruguay, 1972)
Based on the fact that burnt patients have hypercoagulation, a study is being made with respect to the pathogenic fundaments of thromboembolic disease and its clinical manifestations of thromboembolism and disseminated intravascular coagulation. Research is also being conducted as to the causes of death and complications in the evolution of burnt patients. Because of pathogenic conections and similarity in clinical manifestations, the authors suggest the hypothesis that a large part of the complications arising from burns are due to thromboembolic disease.